The function of IRAP+ endosomes in T cells. (October 2022) - Evnouchidou, Irini; Chappert, Pascal; Benadda, Samira; Zucchetti, Andres; Weimershaus, Mirjana; Bens, Marcelle; van Endert, Peter; Guermonprez, Pierre; Hivroz, Claire; Gross, David; Saveanu, Loredana
Abstract : T lymphocytes form an immunological synapse with cells infected by pathogens or cancer cells, after recognition of MHC-epitope complexes by the TCR. The expression of the TCR on the T cell surface, its internalization and its recycling are essential for the TCR signaling pathway. While the proteins implicated in this pathway are well known, there is controversy on the role of TCR endocytosis and recycling in TCR signaling. We identified IRAP+ endosomes as a novel compartment in T cells, that controls TCR signaling. Using mice that are deficient for IRAP only in T cells (IRAP-lox-lox mice crossed with Lck-cre mice) we observed a decreased effector CD8+ T cell number 12 days after immunization with a tumor cell line, as well as increased tumor weight. Since IRAP+ endosomes had never been studied before in T cells, we proceeded to the characterization of this compartment by immunoprecipitations and immunofluorescence not only in mouse transgenic OTI T cells but also in the Jurkat human T cell line. We demonstrated that IRAP colocalizes and coimmunoprecipitates with Rab4, Lck and CD3ζ, the limiting TCR component for signal transduction. In addition, the absence of IRAP inhibits the polarized recruitment of signaling proteins to the synapse, alters the intracellular distribution of CD3ζ, leads to a strong reduction in TCR signaling and results in diminished IL-2 production. According to our results, we suggest that CD3ζ recycles and can signal through IRAP endosomes and that this signaling compartment is essential for the engagement of the TCR-dependent signaling pathways. Our results will help to the understanding of molecular mechanisms implicated in T cell activation, a crucial step of the adaptive immune response on which is based the organism's defense towards pathogens and tumors.